Concordance of somatic mutational profile in multiple primary melanomas. (15th April 2018) - Adler, Nikki R.; McLean, Catriona A.; Wolfe, Rory; Kelly, John W.; McArthur, Grant A.; Haydon, Andrew; Tra, Thien; Cummings, Nicholas; Mar, Victoria J.
Summary: This study aimed to determine the frequency and concordance of BRAF and NRAS mutation in tumours arising in patients with multiple primary melanoma (MPM). Patients with MPM managed at one of three tertiary referral centres in Melbourne, Australia, from 2010 to 2015 were included. Incident and subsequent melanomas underwent mutation testing. Cohen's kappa (κ) coefficient assessed agreement between incident and subsequent primary melanomas for both BRAF and NRAS mutation status (mutant versus wild‐type). Mutation testing of at least two primary tumours from 64 patients was conducted. There was poor agreement for both BRAF and NRAS mutation status between incident and subsequent melanomas (κ = 0.10, 95% CI −0.10 to 0.42; κ = 0.06, 95% CI −0.10 to 0.57, respectively). In view of the low concordance in BRAF mutation status between incident and subsequent melanomas, mutational analysis of metastatic tissue, rather than of a primary melanoma, in patients with MPM should be used to guide targeted therapy.